(untitled) (Estudios Sociales, 2020)
This paper addresses the "Regionalization of Perinatal Attention" in the Greater Buenos Aires. It analyses the state capabilities of Health Regions (HR) facing the challenge of coordinating and articulating work within regional health care/service networks, with emphasis in the Health Region 7. The methodological strategy is qualitative. This includes the survey and systematization of secondary data and the elaboration and analysis of primary data (interviews). The analyses shows limitations and achievements. The HR shows weaknesses in terms of formal institutions and resources, as well as by observing aspects related to the design of the policy and the relationship with the national level. Among the advances, this article shows that there are shared guiding ideas among the actors involved about what is the problem they need to address and how to do it, and that a certain "network conscience" exists. Moreover, the article emphasizes the importance of the individual abilities of managers to establish informal links and solutions "case by case".